The lean Six Sigma pocket toolbook :a quick reference guide to nearly 100 tools for improving process quality, speed, and complexity /Michael L. George ... [et al.]. - Silver, Edward A.(Edward Allen),1937-author
Revised edition of Inventory management and production planning and scheduling.